Cryptanalysis of improved password authentication scheme with smart cards - Pathan, Al-Sakib Khan; Hong, Choong Seon (2008)
The intent of this paper is to present the flaws and weaknesses of Kim et al.'s timestamp-based password authentication scheme using smart cards. We prove that, in spite of the improvement of Yang-Wang-Chang's scheme, Kim et al.'s solution is still vulnerable to a type of forgery attack. We also note down how the flaw could be overcome to ensure better level of security in remote client-server communication procedure.